Blended learning practices in Malaysia higher education: a review - Chan, Man Seong; Fauzi, Mohd Faeiz; Juhari, Siti Norazlina; Aliman, Norazam; Rajoo, Murugan; Abdul Wahab, Noor Maimun; Magiman, Mohamad Maulana (Mathematical and Research Society, 2022)
Blended learning is an innovative strategy for providing engaging and meaningful learning experiences to satisfy student's technology expectations in the highly dynamic digital environment. Despite the fact that there are many studies on higher education instruction abroad, only a small number of blending learning studies have been done in Malaysia higher education. Recognizing the emerging execution of this learning approach, this meta-analysis study serves the purpose of exploring the concepts, the argument, previous studies, the advantages as well as the disadvantages on blended learning practices in Malaysia higher education from 2013 to 2021. The analysis conducted found 10 studies that fit the descriptions. Findings revealed four themes in explaining blended learning practices in Malaysia higher education. Most universities and respondents involved in previous studies are public universities and undergraduate students respectively. This study also examines the methodology used by the previous studies and the main findings of each study conducted. Although this is a relatively small study, it highlights the need for a more different research design to examine the level, frames, and outcomes of blended learning practices in Malaysian universities